Smulyan Lemma and Differentiability of the Support Function (Analysis in Theory and Applications, 2018)
The purpose of this paper is to verify the Smulyan lemma for the supportfunction, and also the Gateaux differentiability of the support function is studied onits domain. Moreover, we provide a characterization of Frechet differentiability of thesupport function on the extremal points.
Keywords: Frechet and Gateaux differentiability; support function; strict convexity; Smulyan lemma.